Nadzir dalam Perspektif Kelembagaan Wakaf di Indonesia - Agung Abdullah (ITB AAS INDONESIA Surakarta, 2020)
The contribution of waqf as an instrument of Islamic philanthropy is seen as important in providing social benefits in meeting the long-term needs of the ummah. The contribution of waqf cannot be separated from the existence of nadzir as a waqf manager. The existence of nadzir (waqf manager) is seen as the responsibility of the party responsible for the productivity of waqf assets previously not included in the terms and laws of traditional waqf in Indonesia. The purpose of this study was to analyze the existence and existence of nadzir in the perspective of waqf institutions in Indonesia. This research uses descriptive analytical method, using secondary data obtained from existing manuscript sources, one of the waqf laws. The data analysis in this study is based on a framework of four levels of institutional economy. The findings in this study are the institutionalization process of nadzir as an official institution in waqf management being analyzed using the four level of institutional economic, the first level I the institutionalization process for waqf managers in Indonesia based on customary law and then Islamic law. The second level formal institutional rules place the law as the formal management rule for waqf after the formation of the Republic of Indonesia. The third Level institutions related to waqf institutional governance that experienced improvements after the issuance of formal rules accompanied by guidance from the waqf accounting standards and the waqf core principles. Fourth Level of institutions related to the management of waqf resources in Indonesia provides wide opportunities for nadzir (waqf managers) to manage waqf. The role of the government in private waqf managers in Indonesia is as protector and issuer of regulations that support waqf productivity.